Dna organization along pachytene chromosome axes and its relationship with crossover frequencies - del Priore, Lucía (2021)
During meiosis, the number of crossovers vary in correlation to the length of prophase chromosome axes at the synaptonemal complex stage. It has been proposed that the regular spacing of the DNA loops, along with the close relationship of the recombination complexes and the meiotic axes are at the basis of this covariation. Here, we use a cytogenomic approach to investigate the relationship between the synaptonemal complex length and the DNA content in chicken oocytes during the pachytene stage of the first meiotic prophase. The synaptonemal complex to DNA ratios of specific chromosomes and chromosome segments were compared against the recombination rates obtained by MLH1 focus mapping. The present results show variations in the DNA packing ratios of macro-and microbivalents and also between regions within the same bivalent. Chromosome or chromosome regions with higher crossover rates form comparatively longer synaptonemal complexes than expected based on their DNA content. These observations are compatible with the formation of higher number of shorter DNA loops along meiotic axes in regions with higher recombination levels.